2022
DOI: 10.1038/s41398-022-02051-4
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and distinguishing indicators of risk for suicide using clinical records

Abstract: Health systems are essential for suicide risk detection. Most efforts target people with mental health (MH) diagnoses, but this only represents half of the people who die by suicide. This study seeks to discover and validate health indicators of suicide death among those with, and without, MH diagnoses. This case-control study used statistical modeling with health record data on diagnoses, procedures, and encounters. The study included 3,195 individuals who died by suicide from 2000 to 2015 and 249,092 randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Based on these findings, we recommend that health practitioners be encouraged to assess for suicide ideation during follow-up visits among all rape survivors, specifically those who reported to have experienced TI and show signs of self-loathing. It is therefore crucial that all rape victims who report to have experienced TI during their ordeal to be assessed for early identification of SI as a global public health concern (ICD 10-CM) and the second leading cause of death worldwide [ 98 , 99 ]. This is especially so in Nigeria, where a study recently reported that the pooled prevalence of suicidal ideation was 9.8% and pooled suicide attempts was 16.2% annually [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, we recommend that health practitioners be encouraged to assess for suicide ideation during follow-up visits among all rape survivors, specifically those who reported to have experienced TI and show signs of self-loathing. It is therefore crucial that all rape victims who report to have experienced TI during their ordeal to be assessed for early identification of SI as a global public health concern (ICD 10-CM) and the second leading cause of death worldwide [ 98 , 99 ]. This is especially so in Nigeria, where a study recently reported that the pooled prevalence of suicidal ideation was 9.8% and pooled suicide attempts was 16.2% annually [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the current state of suicide prevention, there is extensive literature on the effectiveness of its early detection [23,24]. This interest arises from the need to determine the specific characteristics of suicide risk in people with or without psychological problems who receive health care [25][26][27]. Some studies [27,28] show that the identification of suicide risk needs to evolve towards more precise detection strategies than those based on the general factors traditionally associated with suicidal behaviour (mental health problems, chronic illness, loneliness, hopelessness, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…This interest arises from the need to determine the specific characteristics of suicide risk in people with or without psychological problems who receive health care [25][26][27]. Some studies [27,28] show that the identification of suicide risk needs to evolve towards more precise detection strategies than those based on the general factors traditionally associated with suicidal behaviour (mental health problems, chronic illness, loneliness, hopelessness, etc.). For this reason, work is currently underway to construct predictive models using algorithms based on clinical information [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, 0.3% of individuals suffering from non-communicable diseases (such as chronic respiratory diseases, cardiovascular diseases and diabetes) died by suicide within five years after diagnosis, compared to a five-year cumulative risk of 0.1% in the general population [134]. Ahmedani et al recently showed that people who had been diagnosed with cancer, and among them especially those not diagnosed with any mental health condition, were at higher risk of suicide as well [5]. In another study, the relative risk of suicide was found to be as high as 12.6 within one week following a diagnosis of cancer compared to cancer-free individuals [57].…”
Section: Chapter 5 On the Relation Between Medication Prescriptions A...mentioning
confidence: 99%